Analisis Karakteristik Pengunjung dan Tingkat Hunian Kamar di Papyrus Tropical Hotel, Bogor (Analysis Characteristic of Visitors and Occupancy Rates in Papyrus Tropical Hotel, Bogor) - Yudha, Aditya Prima (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2015)
AbstractRoom occupancy rate indicates the volume ofguests at the hotel in a period. Room occupancyrate is the main parameter to see the success ofa service hospitality. The goal of this research isto analyse characteristics of visitors and thedevelopment level of occupancy rooms in thePapyrus Tropical Hotel, making forecastingoccupancy rates for next one year (short term),and analyze the profitability of Papyrus TropicalHotel. Analysis of attitudes of visitors on thisresearch using model multiatribut Fishbein andthe methods of forecasting, was used singleexponential smoothing and double exponentialsmoothing. The results shown that overallvisitors have very positive attitudes towardsPapyrus Tropical hotel with a total score ofFishbein 142,37. Forecasting results for roomoccupancy rate percentages, in 2012 is 47,94percent This result has an increase 5.12 percentfrom 2011 with achievement of operating profitsRp. 983.428.275.Keyword: Occupancy rates, forecasting method,characteristic of visitors